Effectiveness of Pilates-Based Exercises in Managing Chronic Nonspecific Low Back Pain: A Systematic Review - Yu, JaeHo (Journal of Neonatal Surgery, 2025)
Chronic nonspecific low back pain (NSLBP) represents a pervasive musculoskeletal ailment, significantly impacting global public health and socioeconomic productivity. This systematic review synthesizes extant literature to critically evaluate the efficacy of Pilates-based exercises as a therapeutic intervention for individuals afflicted with NSLBP. A comprehensive search strategy was employed across prominent academic databases, referencing key systematic reviews and meta-analyses. Inclusion criteria encompassed randomized controlled trials (RCTs) investigating Pilates interventions for NSLBP, reporting outcomes related to pain intensity and functional disability. Methodological quality was rigorously assessed using established tools such as the Cochrane Risk of Bias tool and the PEDro scale. The synthesized evidence consistently demonstrates that Pilates-based exercises confer statistically significant reductions in pain and improvements in functional capacity among NSLBP populations. While heterogeneity among studies necessitates cautious interpretation, the overall findings underscore Pilates as a viable and beneficial modality in the multifaceted management of chronic low back pain. This review highlights the imperative for future research to adopt more standardized protocols, enhance methodological rigor, and explore long-term outcomes to further solidify the evidence base for Pilates in clinical practice